Paracrine Proangiogenic Function of Human Bone Marrow-Derived Mesenchymal Stem Cells Is Not Affected by Chronic Kidney Disease - Femke C. C. van Rhijn-Brouwer; Bas W. M. van Balkom; Diana A. Papazova; Diënty H. M. Hazenbrink; Anke J. Meijer; Isaac Brete; Vidalmar Briceno; Arjan D. van Zuilen; Raechel J. Toorop; Joost O. Fledderus; Hendrik Gremmels; Marianne C. Verhaar (Stem Cells International)
Background. Cell-based therapies are being developed to meet the need for curative therapy in chronic kidney disease (CKD). Bone marrow- (BM-) derived mesenchymal stromal cells (MSCs) enhance tissue repair and induce neoangiogenesis through paracrine action of secreted proteins and extracellular vesicles (EVs). Administration of allogeneic BM MSCs is less desirable in a patient population likely to require a kidney transplant, but potency of autologous MSCs should be confirmed, given previous indications that CKD-induced dysfunction is present. While the immunomodulatory capacity of CKD BM MSCs has been established, it is unknown whether CKD affects wound healing and angiogenic potential of MSC-derived CM and EVs. Methods. MSCs were cultured from BM obtained from kidney transplant recipients (N=15) or kidney donors (N=17). Passage 3 BM MSCs and BM MSC-conditioned medium (CM) were used for experiments. EVs were isolated from CM by differential ultracentrifugation. BM MSC differentiation capacity, proliferation, and senescence-associated β-galactosidase activity was assessed. In vitro promigratory and proangiogenic capacity of BM MSC-derived CM and EVs was assessed using an in vitro scratch wound assay and Matrigel angiogenesis assay. Results. Healthy and CKD BM MSCs exhibited similar differentiation capacity, proliferation, and senescence-associated β-galactosidase activity. Scratch wound migration was not significantly different between healthy and CKD MSCs (P=0.18). Healthy and CKD BM MSC-derived CM induced similar tubule formation (P=0.21). There was also no difference in paracrine regenerative function of EVs (scratch wound: P=0.6; tubulogenesis: P=0.46). Conclusions. Our results indicate that MSCs have an intrinsic capacity to produce proangiogenic paracrine factors, including EVs, which is not affected by donor health status regarding CKD. This suggests that autologous MSC-based therapy is a viable option in CKD.